STUDI LINGKUNGAN FISIK DI KAWASAN SUB DAERAH ALIRAN SUNGAI GARANG - D. J Jayasamudera; Sodiq Jauhari (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2005)
Sub watershed is a dynamic ecosystem with an interdependent among components. When a watershed experiences an overload canying capacity situation caused by the heavy human activities, the environment's damage will happen especially inphysical and chemical character, land productivity, and the occurrence of flood and draught. All of these, will affect the environment sustainability. This study's objective is to learn the physical changes of garang sub-watershed in Semarang, related to erosion, flood, and draught in this area. Method used is field survey, to identify the erosion level and flodd level, and to measure the draught level. Parameter employed are; rainfall's erosion, land erosion factors, length abd slope level, and management factors of vegetation and erosion. To study the flood factors, parameter used are : rainfalls, volume and surface water level, and maximal and minimal debit of water. The drought factors used for parameter are : rainfalls, width index of leaves, crop/vegetation co efficient, actual evapotranspiration, and crop's evapotranspiration. Analyses method used for measuring the erosion level is USLE method, while for the flood level is letting curb method, and for draught level is'SARRA method. The results show that the actual erosion of garang sub-watershed is between 0.932 ton/ha/year to 1.680.532 ton/ha/year. The flood curb in the catchment's area has commodities is between 0.61 to 0.94.